2008
DOI: 10.1177/102425890801400109
|View full text |Cite
|
Sign up to set email alerts
|

Employee participation, ethics and corporate social responsibility

Abstract: Employee participation is deemed necessary in the name of good governance and corporate social responsibility. For this reason it forms an essential aspect of legal instruments drafted by international public institutions and aimed at multinational enterprises. Despite this, enterprises clearly prefer to take a unilateral approach in the rules they adopt to implement CSR policies, and an individual approach to employee relations, to the detriment of collective labour relations. CSR thus presents two radically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Recently, whistleblowing has come to be recognized as an aspect of corporate governance. As Daugareilh (2008) puts it: "In the name of ethics, individual workers are called upon to step in and report anyone who is likely to damage the interests of the firm". While accepting that the reporting of wrongdoing can be viewed as an aspect of corporate governance, we believe that it is important for both the law and practice of whistleblowing to acknowledge that employers, workers and their trade unions may have conflicting interests.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, whistleblowing has come to be recognized as an aspect of corporate governance. As Daugareilh (2008) puts it: "In the name of ethics, individual workers are called upon to step in and report anyone who is likely to damage the interests of the firm". While accepting that the reporting of wrongdoing can be viewed as an aspect of corporate governance, we believe that it is important for both the law and practice of whistleblowing to acknowledge that employers, workers and their trade unions may have conflicting interests.…”
Section: Introductionmentioning
confidence: 99%
“…The development of soft law instruments has been particularly important in the field of corporate social responsibility which encourages businesses to adopt good practices in the social field on a voluntary basis. Many studies have shown how unreliable such soft law instruments are, to the extent of downgrading European and national labour standards (Daugareilh, 2008), and have stressed the need for a European legal framework concerning corporate transparency and accountability Telljohan et al, 2009).…”
Section: Eu Regulatory Approach In the Area Of Information Consultatmentioning
confidence: 98%
“…The development of soft law instruments has been particularly important in the field of corporate social responsibility which encourages businesses to adopt good practices in the social field on a voluntary basis. Many studies have shown how unreliable such soft law instruments are, to the extent of downgrading European and national labour standards (Daugareilh, 2008), and have stressed the need for a European legal framework concerning corporate transparency and accountability (Schömann et al, 2008;Telljohan et al, 2009). The other particularly worrying aspect of the better regulation agenda is its impact on workers' rights in terms of lowering core labour standards with regard to health and safety in the workplace (Vogel and Van den Abeele, 2010) and information and consultation.…”
Section: The 'Better Regulation/smart Regulation' Miragementioning
confidence: 99%
“…Some of these studies focused on which domain of CSR (e.g., legal, economic, philanthropy, and discretionary) has the strongest impact on employees" attitudes and behaviors (Hsieh & Chan, 2012;Peterson, 2004;Rego, Leal, & Cunha, 2011), whereas others focused on exploring the positive impacts of employees participation in the CSR process (Daugareilh, 2008;Kim, Lee, Lee, & Kim, 2010). Some researchers have highlighted the consideration of how employees distinguish between "authentic and inauthentic" CSR programs (Liedtka, 2008;McShane & Cunningham, 2012).…”
Section: Csr At the Individual Level Of Analysismentioning
confidence: 99%